P21 Lack of NAFLD-related hepatocellular carcinoma surveillance may explain more advanced stage at diagnosis and worse median survival. (20th September 2022) - Hydes, Theresa; Matthews, Charmaine; Kumar, Vinay; Kassab, Mohamed; Blake, Connor Henry; Baggus, Elisabeth; Stern, Nicholas; Cuthbertson, Daniel J; Palmer, Daniel; Johnson, Philip J; Cross, Tim
Abstract : Introduction: Non-alcoholic fatty liver disease (NAFLD) is rapidly emerging as a leading cause of hepatocellular carcinoma (HCC) driven by the dual obesity and type 2 diabetes (T2D) epidemics. Aim: To compare the frequencies of HCC detected outside of surveillance for people with NAFLD vs. other aetiologies of liver disease and to examine possible underlying reasons for this and impact on survival. Methods: A cross-sectional study of patients with HCC detected across one large NHS hospital trust was performed. Data was extracted from existing electronic health records and analysed in SPSS. Results: Overall 184 patients with HCC were identified, 33.2% (n=61) of which had NAFLD. People with NAFLD-HCC were less likely to have been enrolled in an HCC surveillance programme (24.6% vs. 46.7% for other aetiologies of liver disease). We explored the reasons why people with NAFLD-HCC were more likely to present outside of surveillance. A lower proportion of people with NAFLD were known to secondary liver services prior to development of HCC (38.3% vs. 59.3% of people without NAFLD). We also noted a high proportion of people with NAFLD developed HCC without evidence of pre-existing cirrhosis (31.1% vs. 21.0% without NAFLD). No difference in the sensitivity of ultrasound was observed for the detection of HCC between the NAFLD/non-NAFLD groups although this maybe biased by the fact that patients with NAFLD were more likely to have imaging due to symptoms of HCC ( table 1 ). Patients with NAFLD presented with less advanced liver disease (58.3% vs. 45.9% MELD < 9) than people with non-NAFLD-HCC at the time of their cancer diagnosis, however their tumour stage was more advanced (49.2% BCLC stage C/D vs. 37.1%). This was despite comparable frequencies of people with performance status 0 between groups (31.0% NAFLD vs. 29.8% for people without NAFLD), although people with NAFLD were found to have more multimorbidity. Median survival was lower for people with NAFLD HCC vs. non-NAFLD HCC (289 vs. 744 days). Conclusion: Patients with NAFLD are more likely to present with HCC outside of surveillance because they are not known to secondary care or do not have cirrhosis at the time of HCC diagnosis. This will in part account for the fact that people with NAFLD-HCC present with more advanced cancer and have poorer survival. These findings emphasise the need for implementation of widespread screening for NAFLD in the community and risk stratification for HCC.